Ciudad Real and Puertollano. Functional Urban Areas (FUA) and polycentrism in Castilla-La Mancha (Spain) - Cañizares Ruiz, María del Carmen; Martínez Sánchez-Mateos, Héctor Samuel (Documents d'Anàlisi Geogràfica, 2014)
The Functional Urban Areas (FUA) of Ciudad Real and Puertollano are structured by both cities, which are functionally different but keeping growing mutual relations. These areas are located to the south-west of Castilla-La Mancha region, within the province of Ciudad Real. Transport infrastructures, mainly the high-speed rail line, are the main factor that explains the interrelations. The aim of this paper is to characterize both functional areas and to determine the relations between their main urban centres. The methodology combines statistical (population, annual growth rate, linked population, etc.) and empirical analyses, using the cartographic visualization of the main indicators. The results confirm that a joint analysis of both FUA is useful in the context of the polycentrism present in the region of Castilla-La Mancha (Spain) and of the important structuring role of the high capacity transport networks in this case-study.